An Estimation of Wood Volume & Biomass in Some Afforested Sites in Al Ghab Region-Syria - Radwan, Osama; Ali , Wael; Barhoum, Anass (Latakia University Journal -Biological Sciences Series, 2013)
This study is considered a first step in evaluating the success of afforestation applied to some sites in Al Ghab Region. Standing wood volume was estimated for three sites: Almorouj, Hangour and karkat planted with Pinus penia, Pinus brutia and Eucalyptus camaldulensis. Seven different height curves were tested (Korsun, Michailoff, Prodan, Petterson, Parabel, Logarithmic and Freese models) to estimate the height of the planted tree species. Many statistical methods were applied (model bias, precision and accuracy) to test model Validity. The main stand dendrometric parameters of the studied sites were calculated for each tree species. The biomass function of all the tree species investigated was constructed, Almorouj site had the largest amount of biomass (242 ton /ha for eucalyptus trees). Results revealed that Almorouj site had the highest value of wood volume (232 m3/ha for Eucalyptus camaldulensis, 39 m3/ha for pinus pinea, and 59.5 m3/ha for Pinus brutia). Also the most suitable models for the estimation of tree height were Prodan for Pinus penia, freese for Pinus brutia, and parabel for Eucalyptus camaldulensis.